Relationship between Hyperuricemia and Handgrip Strength according to Gender and Menopausal Status in Korean Adults: Analysis of Data from the Korea National Health and Nutrition Examination Survey 2016~2019 - Inyoung KANG; Jaewang LEE (Korean Journal of Clinical Laboratory Science)
This study examined the relationship between the handgrip strength (HGS) and hyperuricemia (HA) in Korean adults using data from the 7th (2016~2018) and 8th (2019) National Health and Nutrition Examination Survey. The population was stratified according to gender and menopausal status. The population of this study comprised 19,441 participants (men=9,077, premenopausal women=5,486, postmenopausal women=4,878). The association between the HGS and HA was evaluated by performing regression analysis and analysis of the covariance (ANCOVA) in each group. Regression analysis showed that the relative HGS was negatively correlated with the blood uric acid (UA) level in men and premenopausal women. Unlike premenopausal women, a negative correlation was confirmed between high-density lipid and UA in men and postmenopausal women. ANCOVA confirmed that metabolic disease-related factors were commonly involved in the relative HGS affected by HA across all groups. Additionally, each group was influenced by different factors beyond common elements. The relative HGS affected by HA was influenced by body mass index and waist circumference, especially in postmenopausal women, which may increase due to estrogen decline following menopause. This study confirmed that individuals with high UA levels may experience a decline in HGS, with the contributing factors varying according to gender and menopausal status.